If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 = (3x + 6) + (6x + 22) Reorder the terms: 52 = (6 + 3x) + (6x + 22) Remove parenthesis around (6 + 3x) 52 = 6 + 3x + (6x + 22) Reorder the terms: 52 = 6 + 3x + (22 + 6x) Remove parenthesis around (22 + 6x) 52 = 6 + 3x + 22 + 6x Reorder the terms: 52 = 6 + 22 + 3x + 6x Combine like terms: 6 + 22 = 28 52 = 28 + 3x + 6x Combine like terms: 3x + 6x = 9x 52 = 28 + 9x Solving 52 = 28 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 52 + -9x = 28 + 9x + -9x Combine like terms: 9x + -9x = 0 52 + -9x = 28 + 0 52 + -9x = 28 Add '-52' to each side of the equation. 52 + -52 + -9x = 28 + -52 Combine like terms: 52 + -52 = 0 0 + -9x = 28 + -52 -9x = 28 + -52 Combine like terms: 28 + -52 = -24 -9x = -24 Divide each side by '-9'. x = 2.666666667 Simplifying x = 2.666666667
| 3(5+x)=31+x | | 51=(2+7x)+(20x+1) | | 50=(8x-6)+(13x+9) | | 87=(8x+2)+(8x+5) | | x-9= | | 8n+8=16 | | 95=(3+8x)+(14x+4) | | 8n+2=16 | | 8n+6=16 | | 8n+6=24 | | 3x+2=7.5 | | 9x+7y=10 | | 57=(9x-2)+(23x-1) | | x+2(x+1)=35 | | 54=(17x+3)+(25x+9) | | 20=(8x+4)+(9x+12) | | 10v+7=8(2u-4)-9 | | 6x+2=8x+14 | | 4(x+1)=8 | | 2p-1=-4p-19 | | (2y-5)-8+y=5 | | 80=(x+9)+(6x-6) | | x^2-42xy-343y^2=0 | | 48=(14x+4)+(24x+2) | | 2b^2+7b=15 | | 2(4p+8)=128 | | x^2+3x-7=0 | | x^2-98=0 | | 2x^2-13x-7=0 | | 4(n+1)+2n=22 | | 3x^2+22x=-40 | | 5x-4=4-3x |